Research on the Robustness of the Roots Waste Heat Power Generation System - Yanjun Xiao (IEEE, 2021)
The reuse of industrial waste heat is an important way to promote energy conservation and reduce emissions. However, low-quality waste heat has a wide distribution range. It is difficult to recover, and the recycling technology needs to be a breakthrough. Therefore, in this paper, we propose a Roots waste heat power generation device which is used to recover low-quality waste heat. However, the relative fluctuation of the air source is greater with the low-quality waste heat than that with the medium- and high-quality waste heat, which makes it difficult for the actual working condition of the device to maintain stability and even causes the generator to cut off automatically. Therefore, it is necessary to perform a study on the robustness of the measurement and control system of the Roots waste heat power generation process and to improve the stability of the device operation. To solve these problems, we propose a control method that combines a robust controller and an internal model controller to improve the robustness of the device. The experimental results showed that the robust internal model controller has a strong anti-interference ability and that the tracking performance is obviously improved.